A Systemic Review of Pharmacological Management of Pediatric Obesity - Surendra Gupta (Journal of Pharmacy and Bioallied Sciences)
Background: There is a growing need for safe and effective treatment due to the rise in child obesity rates worldwide. The effectiveness and safety of pediatric obesity drugs were reviewed in this systematic review based on international research. Techniques: PubMed, Cochrane Library, and Embase searches were performed to locate pediatric randomized controlled trials of antiobesity medications. Demographics, medication effectiveness, adverse events, and quality of life were all analyzed. Findings: There were 12 studies totaling 4,331 children in the review. The age range of the participants was 8.8 to 16.3 years, and their baseline BMI was between 26.2 and 41.7 kg/m2. Medication combinations such as phentermine/topiramate, metformin, extended-release metformin, topiramate, exenatide, and liraglutide were frequently studied. The amount that each medication decreased BMI varied somewhat, with liraglutide exhibiting the most decrease (-5.88 kg/m2). Comparator groups and pediatric antiobesity medication users experienced comparable adverse events and study discontinuation rates. Medication dose adjustments were more common in pediatric cases (10.6% vs. 1.7%; RR = 3.74 [95% CI: 1.51 to 9.26]). Quality of life increased in all trials, however, not specifically for pediatric cases. Conclusion: In conclusion, metformin, topiramate, exenatide, liraglutide, and the combination of topiramate and phentermine may lower BMI in children; however, more studies are required to ascertain their long-term safety and effectiveness. Children and adolescents with pediatric obesity may benefit from a tailored, multidisciplinary strategy that incorporates lifestyle modifications, pharmaceutical therapies, and psychological support to assist manage the condition and enhance the health and well-being of those affected.